A static‐commutated device to contain voltage variations for low‐voltage active users. Issue 8 (16th May 2021) - Casolino, Giovanni Mercurio; Di Nitto, Biagio; Russo, Mario
Abstract: The ever‐wider spread of distributed generation in distribution systems feeds the increasing demand for voltage regulation in low‐voltage networks. For these distribution grids, characterised by simpler structures than medium voltage systems but with a larger number of buses and feeders, voltage control devices have to guarantee fast and reliable operation, as well as economic and simple implementation. A key issue is ensuring adequate voltage amplitude for the active users, which present both load and generation. Variations of active power injections/absorptions by active users can produce long‐duration variations of the voltage amplitudes that exceed normal operating ranges admitted for the feeders, thus causing distributed generation tripping and poor power quality for the loads. This work is intended as 'concept proof' to demonstrate the possibility of obtaining a simple, compact, and cheap device that guarantees adequate voltage amplitudes at low‐voltage user's premises. The device consists of a transformer that can vary its winding arrangements using controlled static switches. A summary of the construction aspects is recalled focussing attention on the control logic and operating characteristics. Various laboratory tests on a prototype are reported, under various operating conditions, highlighting the pros and cons of the considered solution and the margins of improvement.